The development of clinical reasoning in veterinary students - Vinten, Claire (2016)
Clinical reasoning is the skill used when veterinary surgeons make a decision regarding the diagnosis, treatment plan or prognosis of a patient. Despite its necessity and ubiquity within clinical practice, very little is known about the development of clinical reasoning during undergraduate training. Even less is understood about how veterinary schools should be helping students improve this skill. The aim of the research presented within this thesis was to, firstly, examine the development of clinical reasoning ability within veterinary students and, secondly, to investigate possible methods to aid this process. The University of Nottingham School of Veterinary Medicine and Science (SVMS) was used as a case study for this research. In study one, focus groups and interviews were conducted with SVMS staff, students and graduates to investigate the development of clinical reasoning. A curriculum document content analysis was also performed. The findings suggested that clinical reasoning development is not optimal, with alumni facing a steep learning curve when entering practice. These results were used to design study two, in which a simulated consultation exercise utilizing standardised clients was created and implemented for final year students. The success of the simulation was measured using both quantitative and qualitative methods – all of which supported the use of the session for clinical reasoning development. The final study, also building on the findings of study one, aimed to improve the accessibility of veterinary surgeons’ decision-making processes during student clinical extramural studies placements (CEMS). A reflective Decision Diary was created and trialled with third and fourth year SVMS students. Diary content analysis showed the study aim was met, triangulated by survey and focus group findings. During the research, wider issues relating to clinical reasoning integration into veterinary curricula were unearthed. These included low student awareness of the subject and the misalignment between the skill learnt during training and the skill required when in practice. Several recommendations have been made to improve the design of the undergraduate curriculum in relation to clinical reasoning.